Vasile Pârvan - Eugen Simion (Revista de Istorie și Teorie Literară, 2017)
The present text is part of a larger study dedicated to Vasile Pârvan (1882–1927), the Romanian historian and archaeologist, written as an Introduction to a new edition of Vasile Pârvan’s works. A complex portrait of the writer is assembled discussing both his biography and personality, and his works and ideas. Reflected in the works of poets or writers of his time and of following generations, Pârvan’s ideas turned out to be of great importance for the Romanian culture. Getica, a protohistory of Dacia, is the most appreciated work of Pârvan: Reputed historians (C. Giurescu, Daicoviciu, Condurachi, Silviu Dragomir, Alex. Vulpe, Alex. Zub) regarded it as a “monument” of the Romanian culture, a fascinating narrative about a world lost in the apocalypses of protohistory. Literary critics (G. Călinescu, Tudor Vianu, Șerban Cioculescu) evaluated him as a philosopher with ambitions to spiritualize Romanian culture and pointed to the oratoric qualities embedded in his texts as an expression of his talent. The neomodernist and postmodernist poet Nichita Stănescu takes Pârvan as his existential model.